When academic papers’ stated emails do not match authors’ affiliations: A new budding crisis in paper mill-ridden academic publishing? - Teixeira da Silva Jaime Α. (Epistēmēs Metron Logos, 2022)
The email that is indicated on an academic paper usually reflects that of the corresponding author (CA). In some cases, there may be more than one CA, and thus emails. It stands to reason that the email, especially if its is an institutional email, should obligatorily match that of the CA’s affiliation. This report highlights 47 papers, all in Wiley (Hindawi) open access journals, in which the institutional email address suffix does not match or correspond to the stated affiliation indicated as the CA’s affiliation. All papers, except for one, have a stated Chinese academic affiliation. One possibility is that such papers are associated with paper mills, i.e., third party paid services providing content, and possibly even emails to CAs. Editors of the journals in which these papers have been published have the responsibility to investigate.